Anmeldelser - Johnsson, Bengt (Danish Yearbook of Musicology, 1993)
Review of: Bendt Viinholt Nielsen: Rued Langgaards Kompositioner. Annoteret værkfortegnelse. Rued Langgaard's Compositions. An Annotated Catalogue of Works. With an English Introduction. Odense Universitetsforlag. Odense 1991.